Distribution patterns and coincidence of sesamoid bones at metatarsophalangeal joints - Sun, Tao; Zhao, Haitao; Wang, Lingxiang; Wu, Wenjuan; Hu, Wenhai (Surgical and radiologic anatomy (English ed.), 2017)
Purpose Our aim was to identify the incidence and distribution of sesamoid bones plantar to the metatarsophalangeal (MTP) joints in adults, and to evaluate patterns of coincidence among these sesamoid bones. Methods We conducted a retrospective review of 7949 plain radiographs obtained from patients evaluated for foot trauma or symptomology. Associations between the distributions of MTP sesamoid bones as well as the association of age, sex, and laterality with identified prevalence, distribution, and coincidence were evaluated using Spearman’s correlation coefficient. Results Overall, 17,060 sesamoid bones were identified for 9005 MTP joints, with 16 distinctive distribution patterns. Among possible patterns, we identified a prevalence rate of complete absence of MTP sesamoid of 0.04 %, of a single sesamoid at the hallux of 89.08 % of radiographs; and of sesamoid at ≥2 MTP joints of 10.88 %. The presence of a sesamoid at the hallux was consistent, and was not correlated with the presence or absence of a sesamoid bone at one of the other MTP joints ( P > 0.05). However, there was a positive correlation between the presence and absence of sesamoid bones at any two of the other four MTP joints ( P < 0.001). Age was positively correlated with both the total number of sesamoids present ( P < 0.001) and the number of MTP joints with sesamoids ( P < 0.001). Conclusions Information from this study would assist clinicians in the diagnosis of patients presenting with pain and discomfort of the foot after trauma and overuse, as well as contribute a robust data set for research in forensic science and anthropology.